Autonomous Rover for Medical Requirements with Web-based Geospatial Path Planning using GPS (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The Autonomous Rover for Medical Requirements with Web-Based Geospatial Path Planning Using GPS is an intelligent robotic system designed to automate the transportation of medicines, medical equipment, and emergency healthcare supplies. The project aims to improve the efficiency, accuracy, and safety of medical logistics while reducing human effort and delivery time. The rover utilizes Global Positioning System (GPS) technology for real-time location tracking and Web-Based Geospatial Path Planning to determine the shortest and safest route to the destination.The system consists of a microcontroller, GPS module, motor driver, DC motors, ultrasonic sensors, and a wireless communication module. A web application enables users to assign destinations, monitor the rover's movement, and track deliveries in real time. The integrated Obstacle Detection mechanism ensures safe navigation by identifying and avoiding obstacles encountered along the route. This solution is particularly beneficial for hospitals, healthcare campuses, rural medical centers, and disaster-affected areas where timely delivery of medicines is critical. By combining Robotics, Internet of Things (IoT), GPS Navigation, and Geospatial Technologies, the proposed system provides a reliable, cost-effective, and scalable platform for autonomous medical delivery. The project contributes to the advancement of Healthcare Automation, improving operational efficiency and supporting faster emergency response while minimizing manual intervention.